Effect Of Applied Load On The Wear Performance Of 6061 Al/ Nano Ticp/ Gr Hybrid Composites. (2018) - Sozhamannan, G.G.; Mohamed Yusuf, M.; Aravind, G.; Kumaresan, G.; Velmurugan, K.; Venkatachalapathy, V.S.K.
Abstract: For the past few decades, aluminum based hybrid composites have been widely used in many industries, with multiple reinforcements embedded to enhance the wear resistance properties. The wear performances of hybrid composites were prepared by stir casting method and wear performances were evaluated by pin on disc method at dry condition with varying applied load of 40N to 80N and sliding velocity of 1.5 m/s to 4.5 m/s. The wear worn surfaces were analyzed by scanning electron microscope and wear rates were calculated. The experimental results show that wear rate increases in either increasing applied load or sliding velocity and also the applied load and sliding velocity significantly influenced the wear volume loss in hybrid composites. The presence of multiple reinforcements in the matrix enhance the wear performances compared to the 6061 Al alloy.